Facilitated Stories for Change: Digital Storytelling as a Tool for Engagement in Facilitated Discussion for Reduction of Diabetes-Related Health Disparities Among Rural Latino Patients With Diabetes. (November 2021) - Carlson, Lauren Mary; Ridgeway, Jennifer L.; Asiedu, Gladys B.; Wieland, Mark L.; Sia, Irene G.; Porraz Capetillo, Graciela; Bernard, Matthew E.; Hanza, Marcelo M.; Njeru, Jane W.
Introduction: Latino populations, particularly those living in rural areas, experience a disproportionately high prevalence and poorer outcomes of type 2 diabetes mellitus (T2DM). The purpose of this study was to test the acceptability and perceived effectiveness of a group-based, facilitated digital storytelling intervention for T2DM self-management among rural Latino patients. Method: Twenty Latino adults with T2DM participated in facilitated storytelling discussions at two primary clinics. Participants viewed a 12-minute T2DM self-management digital storytelling intervention, followed by a facilitated group discussion. Surveys, observations, and focus groups were used to assess for acceptability and perceived effectiveness of the intervention through descriptive and qualitative analysis, informed by narrative and social cognitive theory. Results: All participants found the intervention interesting and useful and reported improvement in confidence, motivation, and behavioral intentions for T2DM self-management. Themes mapped closely with narrative theory models, further suggestive of the behavior change potential. Discussion: Facilitated discussions may add value to viewing of digital stories and represent a scalable approach to provide culturally congruent health care for Latino patients with diabetes in rural settings. Within the paradigm of group-based diabetes educational programs, this lends itself well to critical transcultural nursing care.